PENGARUH ATRAKSI WISATA DAN FASILITAS WISATA TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA GOA JATIJAJAR KABUPATEN KEBUMEN 2018 - Nurohman, Aji Ima; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
This research is motivated by the growth rate of tourism in Kebumen regency is high and not balanced with the improvement of the quality of existing attractions, either in the form of tourist attractions or tourism facilities. The problem in this research is